Phenotypic and Genotypic Properties of Vibrio cholerae non-O1, non-O139 Isolates Recovered from Domestic Ducks in Germany - Nicola Hirsch; Eva Kappe; Armin Gangl; Keike Schwartz; Anne Mayer-Scholl; Jens Andre Hammerl; Eckhard Strauch (Microorganisms, 2020)
Vibrio cholerae non-O1, non-O139 bacteria are natural inhabitants of aquatic ecosystems and have been sporadically associated with human infections. They mostly lack the two major virulence factors of toxigenic V. cholerae serogroups O1 and O139 strains, which are the causative agent of cholera. Non-O1, non-O139 strains are found in water bodies, sediments, and in association with other aquatic organisms. Occurrence of these bacteria in fecal specimens of waterfowl were reported, and migratory birds likely contribute to the long-distance transfer of strains. We investigated four V. cholerae non-O1, non-O139 isolates for phenotypic traits and by whole genome sequencing (WGS). The isolates were recovered from organs of domestic ducks with serious disease symptoms. WGS data revealed only a distant genetic relationship between all isolates. The isolates harbored a number of virulence factors found in most V. cholerae strains. Specific virulence factors of non-O1, non-O139 strains, such as the type III secretion system (TTSS) or cholix toxin, were observed. An interesting observation is that all isolates possess multifunctional autoprocessing repeats-in-toxin toxins (MARTX) closely related to the MARTX of toxigenic El Tor O1 strains. Different primary sequences of the abundant OmpU proteins could indicate a significant role of this virulence factor. Phenotypic characteristics such as hemolysis and antimicrobial resistance (AMR) were studied. Three isolates showed susceptibility to a number of tested antimicrobials, and one strain possessed AMR genes located in an integron. Knowledge of the environmental occurrence of V. cholerae non-O1, non-O139 in Germany is limited. The source of the infection of the ducks is currently unknown. In the context of the ‘One Health’ concept, it is desirable to study the ecology of V. cholerae non-O1, non-O139, as it cannot be excluded that the isolates possess zoonotic potential and could cause infections in humans.